2014
DOI: 10.1186/1472-6874-14-1
|View full text |Cite
|
Sign up to set email alerts
|

Ways of coping with premenstrual change: development and validation of a premenstrual coping measure

Abstract: BackgroundNegative premenstrual change can result in distress for a significant proportion of women. Previous research has suggested that women employ a range of coping strategies and behaviours in order to manage and reduce premenstrual distress. However, as yet there has been no specific scale available to measure premenstrual coping. This research aimed to develop and validate a measure of premenstrual coping which can be used in future investigations of negative premenstrual experience.MethodsA sample of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
80
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 54 publications
9
80
5
Order By: Relevance
“…Men and women also differ in the clinical symptoms. Men often report more sputum production, whereas health-related quality of life is lower for women than for men with COPD 27. However, in terms of swallowing capacity and dysphagia burden, we found no significant gender differences.…”
Section: Discussioncontrasting
confidence: 73%
“…Men and women also differ in the clinical symptoms. Men often report more sputum production, whereas health-related quality of life is lower for women than for men with COPD 27. However, in terms of swallowing capacity and dysphagia burden, we found no significant gender differences.…”
Section: Discussioncontrasting
confidence: 73%
“…For example, previous literature has indicated that women who experience premenstrual changes can use social withdrawal as means of coping. Such so called 'maladaptive' premenstrual coping processes can appear in such forms as social withdrawal and avoidance of situations (Read et al, 2014). These withdrawals and avoidances may explain what was found in the sample studied here.…”
Section: Discussionsupporting
confidence: 57%
“…It is argued that PMS can lead some women to experience high sensitivity to different external stress and emotions, which can make normal life responsibilities more troublesome than usual (Read et al, 2014). It could be that work-related stress, the quality of the work environment, non-cooperative work organization and other work stresses (in addition to any other life stresses) could be contributing to these adverse effects on work capacity and job performance, and explain the results of work being perceived as making symptoms worse with PMS symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction is reflected by high study retention rates: 91% of women remained in the study suggesting that they valued participating in the trial (Marrazzo et al 2015). Participants extolled the regular health check-ups, HIV testing, and the quality of care received at the clinic and welcomed the travel stipends (ZAR150 = USD $15) disbursed at each visit, but often complained about the lengthy waiting times during clinic consultations (Magazi et al 2014). …”
Section: The Context Of the Lie: An Economy Of Hopefulnessmentioning
confidence: 99%